Clinical Investigation:Epidemiology of Rapidly Growing Mycobacteria Bloodstream Infections. (March 2016) - Rodriguez‐Coste, Michelle A.; Chirca, Ioana; Steed, Lisa L.; Salgado, Cassandra D.
ABSTRACT : Background: : Rapidly growing mycobacteria (RGM) bloodstream infections (BSI) are an emerging problem often associated with therapeutic challenges. We review the epidemiology, treatment and outcomes over a 5‐year period of a heterogeneous group presenting to our institution with RGM BSI. Materials and Methods: : A retrospective cohort study of patients with primary RGM BSI from January 2006‐December 2011 was conducted. Patient characteristics (age, race, sex and comorbidities), infection characteristics (catheter associated, hospital acquired, microbiology and antimicrobial susceptibilities), therapy and outcomes were recorded and compared by species. Results: : Among 32 patients, 33 RGM BSI occurred. Patients had an average of 3‐4 comorbidities, most commonly malignancy (45.5%). Most isolates (30.3%) were Mycobacterium fortuitum or Mycobacterium mucogenicum (27.2%), followed by Mycobacterium abscessus/chelonae (18.2%) and Mycobacterium immunogenum (12.2%). In all, 85% were catheter associated and 27.3% were hospital acquired. Empiric therapy was started in 19 (57.6%) patients and among these, it was adequate (at least 2 active agents based on susceptibilities) in 12 (63.2%). Among 21 patients with outcome data, cure was assumed for 14 (66.7%). One death was attributable to RGM BSI. Cure rates were higher among those who received adequate empiric therapy compared to those who did not (83.3% versus 42.9%). In general, antibiotic susceptibility was favorable across species for clarithromycin, amikacin and imipenem. Conclusions: : RGM BSI occurred in a population with multiple comorbidities, most commonly malignancy, and most were catheter associated. Higher cures were seen among those who received adequate empiric therapy and based on susceptibility data, a broad empiric regimen of clarithromycin, amikacin and imipenem would be expected to be adequate.